Human microRNA‐182‐5p and kinectin 1: Potential biomarkers for prognosis in oral squamous cell carcinoma. Issue 12 (30th September 2021) - Jakob, Mark; Mattes, Lena M.; Unger, Kristian; Kueffer, Stefan; Hess, Julia; Canis, Martin; Schirmer, Markus; Spiegel, Jennifer L.; Haubner, Frank; Ihler, Friedrich; Weiss, Bernhard G.; Kitz, Julia
Abstract: Background: The prognostic impact of hsa‐miRNA‐182‐5p in oral cancer remains unexplored. Therefore, the aim of this study was to investigate the prognostic value of hsa‐miRNA‐182‐5p and its predicted target kinectin 1 (KTN1 ) in oral squamous cell carcinoma (OSCC). Method: Expression level of hsa‐miRNA‐182‐5p was analyzed in tumor tissue ( n = 36) and healthy oral mucosal tissue (n = 17) using quantitative real‐time polymerase chain reaction. Protein level of the predicted target KTN1 was detected via immunohistochemistry. Results were validated in a cohort of The Cancer Genome Atlas (TCGA). Results: After dividing the data into a subgroup with high and low hsa‐miRNA‐182‐5p expression level, a significant better overall ( p = 0.016), recurrence‐free ( p = 0.009), and progression‐free survival ( p = 0.004) was observed in an upregulation of hsa‐miRNA‐182‐5p. Staining intensity of KTN1 showed a reciprocal impact on the prognosis. Validation in a TCGA cohort confirmed these results. Conclusion: Our results indicate hsa‐miRNA‐182‐5p and KTN1 as potential biomarkers for OSCC.